Characterization and Comparison of quality management systems for cosmetic products in the world - Madrigal Redondo, German Leonardo (2021)
The quality management systems are tools that can be implemented in different types of industry with the purpose of achieving improved quality standards on the products or services they develop, mainly looking to satisfy the customer and position themselves in the market with an advantage over the products offered. Within the pharmaceutical industry there are numerous regulations and laws that regulate and supervise the production of these products worldwide, ensuring that the industries dedicated to this area have certain regulations and meet minimum quality objectives, because they are products that have a high impact on human life and their improper use can mean major problems for it. This is why, over the years, organizations have been formed. It corresponds to a bibliographic review of international regulations on the manufacture of cosmetic products. Multiple sources are reviewed, from the original standards that contain the minimum requirements for a company that manufactures this type of product, to reviews by auditing and consulting organizations, as well as research on the same subject. It is important to note that basically all regulations, rules and standards specify the same requirements to meet the needs of the customer, and at the same time, meet the safety and quality of a product that will circulate both in domestic and international markets. In this sense, it is clear that the most widely used standard worldwide is ISO 22716:2007, which is widely disseminated across all continents, and is used as the basis for many of the national regulations implemented in countries. The changes made by local regulations are minimal to the content of the standard, adding some clauses to it, but leaving its basic structure intact.